2011
DOI: 10.4103/0971-9784.81568
|View full text |Cite
|
Sign up to set email alerts
|

Placement of an implantable cardioverter-defibrillator in an infant with congenital long QT syndrome: Anesthetic considerations

Abstract: Sudden cardiac arrest (SCA) in children is a rare, but catastrophic event. Children with cardiac pathology at particular risk include those with congenital long QT syndrome (CLQTS) and hypertrophic cardiomyopathy. CLQTS is a genetic disorder of the cardiac ion channels and is associated with significant risk of malignant ventricular arrhythmias and SCA. For symptomatic, untreated patients, the mortality rate is approximately 20% for the first year and 50% at ten years. Use of an implantable cardioverter-defibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…have successfully given general anesthesia for the placement of an implantable cardioverter-defibrillator in an infant with congenital long QT syndrome with similar history. [ 4 ] The ICD has an important role for SCD prevention in children and adolescents. [ 5 ] Patients with previous history of cardiac arrest and two or more risk factors should be considered for an ICD implantation.…”
Section: Discussionmentioning
confidence: 99%
“…have successfully given general anesthesia for the placement of an implantable cardioverter-defibrillator in an infant with congenital long QT syndrome with similar history. [ 4 ] The ICD has an important role for SCD prevention in children and adolescents. [ 5 ] Patients with previous history of cardiac arrest and two or more risk factors should be considered for an ICD implantation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the reports supporting its safety, [17,18] there are also some concerns regarding regeneration of malignant arrhythmias. [14][15][16] There are several case reports showing the development of intraoperative TdP episodes during sevoflurane anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In their case report, Kansara et al [17] reported the anesthetic considerations in an infant with LQTS. They used sevoflurane not only for induction, but also for maintenance of anesthesia without any adverse effect, considering that sevoflurane has minor effects on cardiac electrophysiology.…”
Section: Discussionmentioning
confidence: 99%